Targeting in social expenditure: the incentive-effects in beneficiary households - Cortez, Rafael (1997)
The focalization of social expenditure acquires special importance in the context of high poverty rates and a tight government budget. This article reviews theoretical concepts on social expenditure and explains the two possible "errors" of a social program: to exclude those who need it and to include those who do not.   The minimization of the cost-effectiveness ratio of social expenditure demands the reduction of these errors and, according to this effort, the article points out the danger of considering the beneficiary as passive agents. The transfers of resources have "incentive-effects" that generates reactions in the population that can harm (or favor) the initial objectives of the program.   In this regard, the authors propose a methodology of analysis in regards to the effectiveness of social programs for children care and transfers on the decision to work by the mother, taking in consideration the incentive-effects already mentioned. Surveys of new homes are being used to evaluate the scope and degree of focalization of Peruvian social expenditure.